CONTRIBUTION OF RAIN-FED RICE FARMING INCOME TO HOUSEHOLD INCOME IN SEKERNAN DISTRICT, MUARO JAMBI REGENCY - yusafriyani, fitra; Wahyuni, Ira; Effran, Endy (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
This research aims to: 1). Describe the business patterns of lowland rice farmers in Sekernan District, Muaro Jambi Regency.2). Analyze the income of lowland rice farming based on existing business patterns in Sekernan District, Muaro Jambi Regency. 3). Analyzing how much income from lowland rice farming based on business patterns contributes to farmers' income in Sekernan District, Muaro Jambi Regency. This research was carried out in Pulau Kayu Aro Village and Tantan Village, Sekernan District, Muaro Jambi Regency. The sampling technique used Simple Random Sampling with a sample size of 92 sample farmers. The sample in this research was Rice Farmers who planted IP 100 or once a year. The census method used in data use. Analysis refers to a quantitative approach, using revenue and income analysis. The research results show that there are 4 business patterns in the research location. Pattern I is lowland rice farming, oil palm farming, Pattern II is lowland rice farming and rubber farming, Pattern III is lowland rice farming, oil palm farming and rubber farming, Pattern IV is lowland rice and other farming, Average income of the largest farmers Lowland rice farming originates from Business Pattern III, namely lowland rice farming, oil palm farming and rubber farming with a nominal value of IDR. 75,885,203/farmer/year. The largest contribution of lowland rice farming income to farmers' total income is in business pattern II, namely lowland rice and rubber farming at 48.7%.